Video analysis evaluation of goal actions using a new tactical analytic approach - Izzo, R.; Gagliardi, M.; Raiola, G.; Cejudo, A.; Hosseini Varde'i, C. (Journal of Physical Education and Sport, 2020)
Match analysis is of great importance for the study of performance at an individual or collective level. In this context, the notational analysis represents an element of self-evaluation to verify what is done in the field by the players in a team sport like football. Several studies have dealt with evaluating: goal scoring, influence 1st victory goal, losing teams winning losses, types of offensive actions. This study aims to assess the ways in which a U16 team has scored goals and how these have evolved over the course of a championship (2017/2018).The matches were resumed and subsequently analysed. The elements taken into consideration were: timing of the goal, type of possession, number of passes, duration of the action, and area of commencement of the action. By category of possession, 3 main categories have been identified: Fast Action (AV, maximum 3 passes), Open Action (AM, at least 4 passes), Set-piece Football (CP). For the area where the possession of the ball began, the areas were divided as follows: Zone 1 defensive, Zone 2 pre-defensive, Zone 3 pre-offensive, Zone 4 offensive. The results showed 19 goals from AV, 13 from AM and 4 from CP; 2 goals from Zone 1, 12 from Zone 2, 13 from Zone 3, 5 from Zone 4. The following differences were detected between the outward and return journeys: average passes decreased from 4.69 to 3.21, average duration of the action decreased from 13.14 to 11.37; 7 more goals from AV the round of return; from Zone 3, 3 goals more in the Round of Return and 6 goals from AV against 1 goal from AM; +4 goals scored, -5 goals conceded, +1 point. All these elements combine to highlight the characteristics of the team and the players, the effectiveness of the training course and the evolution of the variables examined.